Sorting of yeast alpha 1,3 mannosyltransferase is mediated by a lumenal domain interaction, and a transmembrane domain signal that can confer clathrin-dependent Golgi localization to a secreted protein. - Graham, T R (1995)
alpha 1,3 mannosyltransferase (Mnn1p) is a type II integral membrane protein that is localized to the yeast Golgi complex. We have examined the signals within Mnn1p that mediate Golgi localization by expression of fusion proteins comprised of Mnn1p and the secreted protein invertase. The N-terminal transmembrane domain (TMD) of Mnn1p is sufficient to localize invertase to the Golgi complex by a mechanism that is not saturable by approximately 15-20 fold overexpression. Furthermore, the TMD-mediated localization mechanism is clathrin dependent, as an invertase fusion protein bearing only the Mnn1p TMD is mislocalized to the plasma membrane of a clathrin heavy chain mutant. The Mnn1-invertase fusion proteins are not retained in the Golgi complex as efficiently as Mnn1p, suggesting that other signals may be present in the wild-type protein. Indeed, the Mnn1p lumenal domain (Mnn1-s) is also localized to the Golgi complex when expressed as a functional, soluble protein by exchanging its TMD for a cleavable signal sequence. In contrast to the Mnn1-invertase fusion proteins, overexpression of Mnn1-s saturates its retention mechanism, and results in the partial secretion of this protein. These data indicate that Mnn1p has separable Golgi localization signals within both its transmembrane and lumenal domains.